Fisetin Protects DNA Against Oxidative Damage and Its Possible Mechanism - Tingting Wang; Huajuan Lin; Qian Tu; Jingjing Liu; Xican Li (Tabriz University of Medical Sciences, 2016)
Purpose: The paper tries to assess the protective effect of fisetin against •OH-induced DNAdamage, then to investigate the possible mechanism.Methods: The protective effect was evaluated based on the content of malondialdehyde(MDA). The possible mechanism was analyzed using various antioxidant methods in vitro,including •OH scavenging (deoxyribose degradation), •O2- scavenging (pyrogallolautoxidation), DPPH• scavenging, ABTS•+ scavenging, and Cu2+-reducing power assays.Results: Fisetin increased dose-dependently its protective percentages against •OH-inducedDNA damage (IC50 value =1535.00±29.60 μM). It also increased its radical-scavengingpercentages in a dose-dependent manner in various antioxidants assays. Its IC50 values in•OH scavenging, •O2- scavenging, DPPH• scavenging, ABTS•+ scavenging, and Cu2+-reducing power assays, were 47.41±4.50 μM, 34.05±0.87 μM, 9.69±0.53 μM, 2.43±0.14μM, and 1.49±0.16 μM, respectively.Conclusion: Fisetin can effectively protect DNA against •OH-induced oxidative damagepossibly via reactive oxygen species (ROS) scavenging approach, which is assumed to behydrogen atom (H•) and/or single electron (e) donation (HAT/SET) pathways. In the HATpathway, the 3',4'-dihydroxyl moiety in B ring of fisetin is thought to play an importantrole, because it can be ultimately oxidized to a stable ortho-benzoquinone form.